Plant venereal diseases insights from a messy metaphor - Antonovics, Janis (The New phytologist, 2005)
The concept of plant venereal disease is examined from definitional, operational and axiomatic viewpoints. The transmission of many plant pathogens occurs during the flowering phase and is effected either by pollinators or by wind dispersal of spores from inflorescences. Attraction of insects by pseudo-flowers or sugary secretions also serves to spread many diseases. Given the diversity of processes involved, a simple all-encompassing parallel with animal venereal diseases is not possible. Operationally establishing the routes of disease transmission, as well as quantifying the relative magnitudes of these different routes, remains critical for understanding disease dynamics and controlling spread in agricultural contexts. From an axiomatic viewpoint, sexually transmitted diseases are characterized by frequency-dependent transmission, transmission in the adult stage, and by virulence effects involving sterility rather than mortality. These characteristics serve to differentiate the dynamics and evolution of sexually transmitted diseases from that of other diseases and are features that are also shared by many pollinator-transmitted diseases. However, the majority of plant diseases that involve the reproductive structures show a rich biology that defies easy categorization. The experimental convenience of plants and their pathogens is likely to play an important role in understanding the evolution of disease traits, irrespective of what descriptive terms are applied to the natural history of the transmission process